Copula Deletion in San Andresan Creole - Suárez-Gómez, Cristina; Chamorro-Díaz, Margarita María (Miscelánea: A Journal of English and American Studies, 2020)
This paper deals with copula deletion in San Andresan Creole (SAC), an English-lexifier creole spoken in the Caribbean islands of Colombia. One of the most widely studied features of Caribbean creoles is the variable use of the verb BE (see Labov 1969; Holm 1976; Rickford 1996; Sharma and Rickford 2009; Michaelis et al. 2013, etc.). We aim to establish the linguistic and social determinants of observable variation in the copula system of SAC. To this end we will look primarily into BE presence (e.g. dei waz der an di fishin graun ‘they were there at the fishing ground’) vs BE deletion (e.g. shi veri hongri ‘she (was) very hungry’), and its distribution according to linguistic variables (e.g. grammatical context, grammatical category and grammatical person of the subject, and tense). While bearing in mind the complex linguistic situation in Colombia, and in the Caribbean generally, these findings provide a more complete picture of variation in the use of BE in SAC and will offer valuable evidence regarding the vitality, unity and hetereogeneity of this creole. The probabilistic analysis of the results shows that grammatical context and grammatical category of the subject determine variation in this domain of grammar, repeating a recurrent pattern shown by other Atlantic creoles. These findings provide a more complete picture of variation in the use of BE in SAC and offer valuable evidence regarding the vitality, unity and heterogeneity of this creole.
Keywords: San Andresan Creole; Copula deletion; Grammatical variation; Grammatical context; Subject category; Grammatical person; Tense